2015
DOI: 10.1055/s-0035-1553266
|View full text |Cite
|
Sign up to set email alerts
|

Importance of Transvaginal Elastography in the Diagnosis of Uterine Fibroids and Adenomyosis

Abstract: The "age index" shows that normal uterine tissue has a certain age-dependent stiffness that increases with age. The "lesion index" allows for the assessment of the presence of a uterine fibroid or adenomyosis and helps to differentiate between both focal findings. Thus the use of elastography in addition to conventional ultrasound could help to diagnose uterine focal lesions and may be useful in preoperative planning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
33
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 18 publications
4
33
2
Order By: Relevance
“…In a recent study, it was shown that elastography was able to identify clear discriminating characteristics of the uterus, fibroids, and adenomyosis, and elastographically based diagnoses were in excellent agreement with those of magnetic resonance imaging 17 . In another study, the authors concluded that elastography allows for the assessment of the presence of a uterine fibroid or adenomyosis and helps differentiate between both focal findings 23 . Interestingly, it was also shown that the stiffness of normal uterine tissue increased with age 23 .…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…In a recent study, it was shown that elastography was able to identify clear discriminating characteristics of the uterus, fibroids, and adenomyosis, and elastographically based diagnoses were in excellent agreement with those of magnetic resonance imaging 17 . In another study, the authors concluded that elastography allows for the assessment of the presence of a uterine fibroid or adenomyosis and helps differentiate between both focal findings 23 . Interestingly, it was also shown that the stiffness of normal uterine tissue increased with age 23 .…”
Section: Discussionmentioning
confidence: 96%
“…17 In another study, the authors concluded that elastography allows for the assessment of the presence of a uterine fibroid or adenomyosis and helps differentiate between both focal findings. 23 Interestingly, it was also shown that the stiffness of normal uterine tissue increased with age. 23 These studies generally support our findings that elastography may be useful in the assessment of uterine disorders.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As of now, it has mainly been utilized in classification of tumors and tissue changes of the breast, prostate, and liver. Furthermore, initial studies have recently been published on evaluation of cervical stiffness and preterm labor or uterine fibroids and adenomyosis …”
mentioning
confidence: 99%
“…Furthermore, initial studies have recently been published on evaluation of cervical stiffness and preterm labor or uterine fibroids and adenomyosis. 12,13 To the best of our knowledge, elastography has so far not been investigated to evaluate postpartum pelvic floor trauma. The aim of our study was to introduce elastography as a new method for assessment of pelvic floor trauma after childbirth.…”
mentioning
confidence: 99%